HARD AND SOFT POWER IN DEMOCRATIC SYSTEMS: A COMPARATIVE ANALYSIS - Shakhzodbek Makhmudov (American Journals Publishing, 2025)
This article examines the concepts of soft and hard power in international relations, with a focus on domestic institutions within the context of democratic systems. It relies on Joseph Nye’s seminal work and more recent empirical indexes to critique the classical dualism of statecraft’s coercive or persuasive nature. It compares the United States, France, Germany, and Japan to argue that political systems, whether presidential or parliamentary, federal or unitary, influence the projection and efficacy of power abroad. The article argues that power should not be conceptualized merely as an asset stock, but rather as a process situated within political institutions, the intersection of strategic alignment, and continuity in leadership. It offers a new approach with the “Smart Power Governance Matrix” to analyse how democracies apply soft and hard power through institutional integration, multilateralism, and enduring foreign policy. The results highlight the need to redefine the discourse on democracy and power in global politics by relocating analysis beyond fixed criteria to situationally defined frameworks of state capabilities within their governance systems.
Keywords: Soft power, hard power, political system, smart power, political transition, democracy, power projection.